Theranostics: Boosting Postsurgical Outcomes of Orthotopic Hepatocellular Carcinoma via an EpCAM‐Targeting Theranostic Nanoparticle (Part. Part. Syst. Charact. 8/2019). (22nd August 2019) - Hu, Min; Wang, Kun; Shang, Wenting; Han, Ziyu; Jiang, Hongmei; Fang, Chihua; Tian, Jie
Abstract : In article number 1900085, Chihua Fang, Jie Tian, and co‐workers develop a multifunctional epithelial cell adhesion molecule (EpCAM)‐targeting nanoparticle with triple‐modality visualization, uniting magnetic resonance, photoacoustic, and fluorescence imaging for the high precision diagnosis of hepacellular carnicoma (HCC) and intraoperative imaging guidance for accurate hepatectomy. As an interoperative adjuvant strategy, the photothermal therapy (PTT) capability allows for further eliminating possible microscopic tumor residues and boosting HCC surgery outcomes.